Water Mass and Indirect Estimation of Turbulent Mixing Based on Observational CTD Yoyo Data in Flores Sea Waters, Indonesia - Harsono, Gentio; Yuliardi, Amir Yarkhasy; Wirasatriya , Anindya; Purwanto, Budi; Cabral, Mario (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research Three distinct water layers were identified: surface (0-50 m), thermocline (50-180 m), and deep (>180 m). The thermocline layer is the most stable, with high Brunt-Väisälä frequency and low Thorpe displacement values. The highest energy dissipation rates were observed in the thermocline layer. Vertical diffusivity values were highest in the thermocline layer and decreased with depth.     Abstract The Flores Sea is on the western ITF trajectory connecting the Pacific and Indian oceans. Identification and quantification of turbulent mixing of water masses in the Flores Sea are essential for analyzing large-scale ocean circulation processes, including the circulation of the Indonesian ocean interior. However, direct estimations of turbulent mixing in the Flores Sea as a part of the ITF are underestimated. This research aims to determine water conditions, stratification, and water mass structures. This research used data obtained from the CTD instrument applying a Yoyo casting method deployed in March − April 2023. On the other hand, the Thorpe method was used to estimate turbulent vertical mixing based on the values ​​of energy dissipation and vertical diffusivity. The waters are stratified into three layers, mixed layer (1−50 m), thermocline layer (50−180 m), and deep layer (180−500 m). The CTD data showed the presence of a stable thermocline layer dominated by ITF water masses carrying water masses from the Pacific Ocean (North Pacific Intermediate Water (NPIW) and North Pacific Subtropical Water (NPSW)) from the western ITF path. The energy dissipation value obtained at the study site was about 3.36E-07 W Kg-1 and the vertical diffusivity value was approximately 5.25E-05 m2s-1. The thermocline layer showed a large energy dissipation value which was strongly associated with the friction of the ITF, suggesting that turbulent mixing in this region is primarily driven by the interaction of ITF water masses with the surrounding environment.